MORAL EDUCATION TOWARD THE DIGITAL REVOLUTION: (COMPARATIVE ANALYSIS OF THE ISLAMIC AND WESTERN PHILOSOPHY PERSPECTIVE) - Atika Rofiqatul Maula (FORPIM PTKIS ZONA TAPAL KUDA, 2022)
ABSTRACTThe development of digital flows in many countries has grown rapidly, one of that is the way of interacting between people, from interacting directly to virtual interactions. The shifting certainly makes access between people easier and faster, but it can't be avoided that it can also lead to negative actions. Education needs to pay serious attention to this, how students maintain good character in a virtual interaction or digital world. The step taken by education stake holders is to reflect on how to embed moral education in students. This study aims to describe and analyze moral education based on a philosophical perspective from Islamic and western views. Literature review research is the method of this study by using content analysis techniques. To complete this study, data was collected through various sources of relevant studies from books, journals and news. The results reveal that moral education in the western view can lead students to explore life skill education in social life. Meanwhile, according to the Islamic view, moral education also has implications for spirituality aspects, that make the students who have good morals, faith and takwa.Keywords: Digital Revolution, Moral, Education.